THE EFFECTS OF TYPES OF FEEDBACK ON STUDENTS' REVIEWING PROCESS IN AN ONLINE SCAFFOLDED PROCESS WRITING CLASSROOM - Wardatul Akmam Din; Suyansah Swanto; Megawati Soekarno; Noraini Said, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
There has been growing evidence that the lack of academic writing skills among university students who learn English as a Second Language (ESL) affects their overall academic performance. Higher education ESL students often find writing academic essays a complex process and hence struggle with academic writing convention issues. However, in order to encourage these students’ to be autonomous in their English academic writing, explicit and supportive instruction is necessary on the teacher’s part. This study aims to investigate thirty Foundation students’ revision activities pre- and post-intervention and whether there are any changes in their reviewing activities after being exposed to the intervention for twelve weeks. The reviewing activities were categories and analysed for inter-correlations. It is found that the students’ revision activities at first seem to concentrate mostly on Surface Changes-Meaning Preserving Changes activities. However, this changes in the second half of the intervention period where they seem to perform more Meaning Changes-Microstructure Changes and the least is Surface Changes-Formal Changes.